(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
Application of three combinations of lactic acid bacteria (Lactobacillus plantarum, Lactobacillus rhamnosus), phototrophic bacteria (Rhodopseudomonas palustris) and yeast (Saccharomyces cerevisiae) with sugar cane molasses, marked as: EM1, EM5 and EM AGRO, against the phytopathogenic fungi of tomato and pepper: Fusarium oxysporum, Alternaria alternata, Botrytis cinerea, Colletotrichum sp., Verticilium dahliae and Pythium aphanidermatum was evaluated in vitro and in vivo. A combination of bacteria and yeast named EM5 showed the highest mycelium growth inhibition against B. cinerea (38.4%) in a double agar diffusion test. In a microdilution test, the combination EM1 showed the highest inhibitory effect on B. cinerea (MIC 1x10-3 μl/ml), while EM5 showed a similar inhibitory effect towards F. oxysporum, A. alternata and Colletotrichum sp. (MIC 10 μl/ml). The use of EM1 (in concentrations 10 and 100 μl/ml) and EM AGRO (10 μl/ml) is recommended for tomato seedling protection. ЕМ1 (100 μl/ml), ЕМ5 and ЕМ AGRO (10 μl/ml) are recommended for pepper seedling protection.